2000
DOI: 10.1007/bf02868029
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic consumption patterns and drug leftovers in 6000 Brazilian households

Abstract: Worldwide data indicate that antibiotics are frequently used indiscriminately. The present study used a questionnaire in an attempt to quantify and qualify outpatient antibiotic consumption habits, including when the drug was used, who recommended it, and to what extent treatment was completed, and to question householders on the presence of antibiotics in their homes, including leftovers from previous treatments. The questionnaire was distributed to residents of 6000 households that made up a representative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…50% of respondents studied. Indeed, possession of leftover antibiotics and their use have been reported previously in a number of developed and developing countries [2,[8][9][10][11][12][13][14]. A survey performed previously revealed the percentage of respondents who saved antibiotics and used them on future occasions ranged from 4% in the UK to 41% in Italy [15].…”
Section: Discussionmentioning
confidence: 90%
“…50% of respondents studied. Indeed, possession of leftover antibiotics and their use have been reported previously in a number of developed and developing countries [2,[8][9][10][11][12][13][14]. A survey performed previously revealed the percentage of respondents who saved antibiotics and used them on future occasions ranged from 4% in the UK to 41% in Italy [15].…”
Section: Discussionmentioning
confidence: 90%
“…Of the seven compliance estimates using inperson questionnaires, six estimates [24,48,58] defined compliance as finishing the antibiotic course, and three studies [4,23,25,47]. Five of the six studies that used selfadministered questionnaires to assess compliance defined it as completing the antibiotic course [27,31,40,44,57], whilst one study did not state its definition of compliance [46]. Pill counts were used to assess compliance in 10 estimates.…”
Section: Compliance With Therapymentioning
confidence: 99%
“…The study populations were geographically diverse, with only one study conducted in the United States [54] and one-half conducted in developing nations [4,18,46,49,50], including Thailand, Ethiopia and Brazil. All studies used subjective measures to assess compliance, including self-administered questionnaires [27,46,54], telephone interviews [4,47,50] and in-person interviews [18,49,58]. Assessment of leftover antibiotic use involved recall of an antibiotic prescription in the past or over a defined period of time, and actual leftover definitions varied slightly across studies.…”
Section: Leftover Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In b-lactam group, AMX is one of the most widely used antibiotic drugs [7], which is widespread in the aquatic environment including wastewater as reported. And it has been reported that AMX concentration in the raw antibiotic wastewater reach to 171 mg L À1 [8].…”
Section: Introductionmentioning
confidence: 99%